Public Policy Barricading the Foreign Arbitral Award: A Comparative Analysis between UK, USA & France - Sharif, Ammara; Ali, Shan; Iqbal, Amina; Khalid, Mahrukh (International Journal of Criminology and Sociology, 2021)
The concept of public policy in International Arbitration is still extremely contentious, controversial, and complicated in modern times. Although legislation related to arbitration and practise have attempted to harmonise public policy so that parties may benefit from a globally recognised idea, judicial courts have made this effort almost difficult by giving a very loose & broad definition in the name of public policy. Moreover, the New York Convention gives little direction to national courts on how to interpret the public policy claim. In the name of local contract laws and fundamental principles of a nation, judge keeps hampering the enforcement of foreign award. Internal Law Association attempted to resolve this contention but couldn't come up with a definite definition which limits the policy in a closed structure. Despite the ambiguity of the issue, national courts in most developed arbitral countries interpret public policy narrowly. Because industrialised countries' courts typically see arbitral awards as a separate aspect of public policy; they are pro-enforcement. In this article we will comprehensively elaborate this attitude, legislation and case law study of developed nations like USA, UK and France.